Common hand and wrist conditions: creation of UK research priorities defined by a James Lind Alliance Priority Setting Partnership. Issue 3 (26th March 2021) - Karantana, Alexia; Davis, Tim; Kennedy, Donna; Larson, Debbie; Furniss, Dominic; Grindlay, Douglas J; Cowan, Katherine; Giddins, Grey; Jain, Abhilash; Trickett, Ryan W
Abstract : Objective: Prioritisation of important treatment uncertainties for 'Common Conditions Affecting the Hand and Wrist' via a UK-based James Lind Alliance Priority Setting Partnership. Setting: This process was funded by a national charitable organisation and based in the UK. Participants: Anyone with experience of common conditions affecting the adult hand and wrist, including patients, carers and healthcare professionals. All treatment modalities delivered by a hand specialist, including therapists, surgeons or other allied professionals, were considered. Interventions: Established James Lind Alliance Priority Setting Partnership methods were employed. Electronic and paper questionnaires identified potential uncertainties. These were subsequently confirmed using relevant, up-to-date systematic reviews. A final list of top 10 research uncertainties was developed via a face-to-face workshop with representation from patients and clinicians. Impact of research was sought by surveying hand clinicians electronically. Outcome measures: The survey responses and prioritisation—both survey and workshop based. Results: There were 889 individually submitted questions from the initial survey, refined to 59 uncertainties across 32 themes. Eight additional uncertainties were added from published literature before prioritisation by 261 participants and the workshop allowed the final top 10 list to be finalised. The top 10 has so far contributed to the award of over £3.8 million of competitively awarded funding. Conclusions: The Common Conditions in the Hand and Wrist Priority Setting Partnership identified important research questions and has allowed research funders to identify grant applications which are important to both patients and clinicians